Molecular typing of nosocomial strains of Legionella pneumophila by arbitrarily primed PCR. - Grattard, F (1996)
Arbitrarily primed PCR with two different primers was compared with ribotyping and monoclonal antibody analysis for typing Legionella strains. Applied to 11 epidemiologically unrelated strains, arbitrarily primed PCR resulted in an index of discrimination of 100% with both primers. It was found able to identify an epidemic clone of Legionella pneumophila serogroup 1 that was isolated from both patients and a hot water circuit of the same hospital.